Polyvascular Subclinical Atherosclerosis: Correlation Between Ankle Brachial Index and Carotid Atherosclerosis in a Population-Based Sample. (May 2023) - Vila, Maria del Mar; Igual, Laura; Remeseiro, Beatriz; Elosua, Roberto; Ramos, Rafel; Valdivielso, Jose M; Martí-Lluch, Ruth; Marrugat, Jaume; Grau, Maria
We assessed the correlation between the biomarkers of lower limb atherosclerosis (eg, ankle-brachial index [ABI]) and of carotid atherosclerosis (eg, common carotid intima-media thickness (IMT) and presence of atherosclerotic plaque) in a population-based cohort from Girona (Northwest Spain) recruited in 2010. Ankle-brachial index and carotid ultrasound were performed in all participants. Generalized additive multivariable models were used to adjust a regression model of common carotid IMT on ABI. Logistic regression multivariable models were adjusted to assess the probability of carotid plaque in individuals with peripheral artery disease. We included 3307 individuals (54.2% women), mean age 60 years (standard deviation 11). Two patterns of association were observed between subclinical biomarkers of atherosclerosis at the lower limb and carotid artery. Ankle-brachial index and common carotid IMT showed a linear trend in men [beta coefficient (95% confidence interval) =-.068 (−.123; −.012); P = .016]. Women with peripheral artery disease presented with high risk of atherosclerotic plaque at the carotid artery [Odds ratio (95% confidence interval) = 2.61, (1.46; 4.69); P = .001]. Men showed a significant linear association between ABI levels and common carotid IMT values. Women with peripheral artery disease presented with high risk of atherosclerotic plaque at the carotid artery.